2020
DOI: 10.1017/s1751731119002283
|View full text |Cite
|
Sign up to set email alerts
|

Effects of time-based feed restriction on morbidity, mortality, performance and meat quality of growing rabbits housed in collective systems

Abstract: In rabbit farms, quantitative feed restriction in the post-weaning period is widely used with the aim of reducing the impact of digestive diseases, whereas less information is available about feed restriction strategies based on the reduction of access time to feeders in different housing systems. This study compared morbidity, mortality, growth performance, carcass characteristics and meat quality of 368 crossbred rabbits fed ad libitum (L) or subjected to a time-based feed restriction programme (R) and house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 18 publications
4
23
0
1
Order By: Relevance
“…For fattening rabbits, feed restriction during rearing period allowed uniformity in body weight and decreased neonatal mortality (Rommers et al2001). While a moderate feeding restriction may improve some sperm morphologic characteristics, as well as fertility in male rabbits (Pascual et al 2016), it seems that restriction strategies have shown less beneficial effects and even more for rabbit does (Birolo et al 2020). Restricting feeding during different stages of pregnancy, even if it does not strongly affect growth of young rabbits, may delay placental growth, decrease the offspring survival and birth weight (Rommers et al 2004; Matsuoka et al 2012; Manal, Tony, and Ezzo 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For fattening rabbits, feed restriction during rearing period allowed uniformity in body weight and decreased neonatal mortality (Rommers et al2001). While a moderate feeding restriction may improve some sperm morphologic characteristics, as well as fertility in male rabbits (Pascual et al 2016), it seems that restriction strategies have shown less beneficial effects and even more for rabbit does (Birolo et al 2020). Restricting feeding during different stages of pregnancy, even if it does not strongly affect growth of young rabbits, may delay placental growth, decrease the offspring survival and birth weight (Rommers et al 2004; Matsuoka et al 2012; Manal, Tony, and Ezzo 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For fattening rabbits, feed restriction during rearing period allowed uniformity in body weight and decreased neonatal mortality (Rommers et al, 2001). While a moderate feeding restriction may improve some sperm morphologic characteristics, as well as fertility in male rabbits (Pascual et al, 2016), it seems that restriction strategies have shown less beneficial effects and even more for rabbit does (Birolo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Gratta et al (2019) stated that late-restricted (from 27 to 37 days of age) chickens had a significantly lower carcass weight and breast proportion, while earlyrestricted (from 13 to 23 days of age) chickens had an intermediate carcass weight and breast percentage compared to those of ad libitum fed chickens. In rabbits, Birolo et al (2016;2020a), Alabiso et al (2017), and Chodova et al (2019) did not observe a significant effect of FR on carcass composition, while Gidenne et al (2012), Chodova et al (2016) and Birolo et al (2020b) observed lower DOP in restricted rabbits. In our recent experiment with nutrias, FR increased the hind part and perirenal fat percentage (Tumova et al 2021a).…”
mentioning
confidence: 81%
“…In this trial was not observed any difference among groups, that may have been because the mortality was moderate (12.8% on average). In fact, in other studies the feed restriction did not reduce the mortality rate below 9-17% when that of control group was between 15 and 23% (Gidenne et al, 2009c;Knudsen et al, 2014;, or even tended to increase it (Birolo et al, 2020), although other authors found very positive effects (Birolo et al, 2016;Romero et al, 2010), even compared to a medicated feed (Alabiso et al, 2017). There is no clear explanation for these differences among studies, and a combination of factors like the farm health status, diet, method of feed restriction employed, or type of housing might be behind them.…”
Section: Effect Of Feed Restriction (Experiments 4)mentioning
confidence: 88%
“…However, other authors (Gidenne et al, 2012;Knudsen et al, 2017;Birolo et al, 2020) reported an impairment of the carcass yield. Normally, the impairment is related to higher weight of the full tract associated with the development of internal organ such as small and large intestines, caecum and the liver during the restriction period and refeeding (Tumová et al, 2016).…”
Section: Effect Of Feed Restriction (Experiments 4)mentioning
confidence: 91%